2016
DOI: 10.1063/1.4960434
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure phase diagram of crystalline benzene from quantum Monte Carlo

Abstract: We studied the low-pressure (0–10 GPa) phase diagram of crystalline benzene using quantum Monte Carlo and density functional theory (DFT) methods. We performed diffusion quantum Monte Carlo (DMC) calculations to obtain accurate static phase diagrams as benchmarks for modern van der Waals density functionals. Using density functional perturbation theory, we computed the phonon contributions to the free energies. Our DFT enthalpy-pressure phase diagrams indicate that the Pbca and P21/c structures are the most st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 75 publications
(170 reference statements)
3
17
0
Order By: Relevance
“…Fixed-node DMC is the most accurate known method for evaluating the total energies of continuum systems of more than a few tens of interacting quantum particles [28][29][30][31][32][33]. Recently, it has been indicated that DMC can provide an accurate description of the phase diagram of solid molecular hydrogen [34].…”
Section: Introductionmentioning
confidence: 99%
“…Fixed-node DMC is the most accurate known method for evaluating the total energies of continuum systems of more than a few tens of interacting quantum particles [28][29][30][31][32][33]. Recently, it has been indicated that DMC can provide an accurate description of the phase diagram of solid molecular hydrogen [34].…”
Section: Introductionmentioning
confidence: 99%
“…[20]). We are not concerned with all solid phases of benzene [21]; however, for the range of pressures we are considering in this work (the moderate pressure regime: p < 20 GPa), the unit cell of solid benzene has the Pbca Z = 4 structure [22]. As can be seen from Fig.…”
Section: Treatment Of the Results -The Supercooling ∆Tmentioning
confidence: 99%
“…The universal-kernel descriptions simplify an analysis of the nature of binding. Figure 8 illustrates how having efficient determinations of nonlocal-correlation contributions equations (119) and (120) can provide a spatial mapping of the nature of binding, here explored for the case of a graphene bilayer. The left panel shows a mapping of the full E nl c binding contribution; such mapping was introduced and discussed in references [55,57,58] and can be supplemented by a couplingconstant scaling analysis that isolates the kinetic-correlation energy binding component [14].…”
Section: Electrodynamics Interpretation Of Consistent Vdw-df Designsmentioning
confidence: 99%
“…This is, for example, relevant for development of ionic liquids, batteries, thermo-electrics, and organic solar-cell materials [98,[113][114][115][116][117][118]. The vdW-DF-cx version tends to overestimate the binding energy in some layered systems [12,119,120], but remains accurate on structure [68,121]. It works for both intraand for inter-molecular bonds [9, 11, 13-15, 44, 122-124], for hybrid organic-inorganic perovskites [125], and for analysis and design of porous-materials gas storage [11,45,[126][127][128] and of surface pacification [129].…”
Section: Introductionmentioning
confidence: 99%